User Experience Design of Web-Based BPKAD Asset Mapping using Kansei Engineering - Indra Griha Tofik Isa; Anitawati Mohd Lokman; Leni Novianti; Indri Ariyanti; Rika Sadariawati; Afiza Ismail; Azhar Abd Aziz (NAROTAMA UNIVERSITY, 2023)
User Experience (UX) is an integral part of software development, one of which is web-based mapping. Several factors that affect that UX is acceptable to users include visual aesthetics, ease of menu hierarchy, component layout and display coloring. There are several things that are not implied in UX development, namely the psychological factor of the user in which there is emotion and feeling. This research is located at BPKAD Palembang City which has purposing to 1) Analyzing user psychological factors in terms of feelings and emotions in designing web-based UX for the Palembang City BPKAD Regional Asset Mapping, 2) Interpreting user psychological factors into web-based design elements of the Palembang City BPKAD Regional Asset Mapping. The research stages include determining Kansei Word; Structuring SD Scale; Collecting and Validating Web-Based Mapping Specimen; Category and Item Design Classification; Participant Data Evaluation; Data Analysis and Defining Design Elements. The final result is 5 emotion concepts, these are dynamic & well-organized concept, refreshing concept, spacious concept, professional concept and nautical-look concept. The DEs generated from PLS analysis for dynamic & well-organized concepts are 27 DEs, refreshing concept is 15 DEs, spacious concept is 17 DEs, professional concept is 18 DEs and nautical-look concept is 18 DEs.